La suspensión temporal de la pensión alimenticia por parte del alimentante cuando se ha cumplido extrajudicialmente con la obligación - Freire Vivero, Lily Nathaly (2017)
We define the right to food as the parent's ability to provide food, clothing, education, etc., to their children with the sole purpose of meeting pressing needs for their existence. The nature of this right is to protect the child or adolescent and thus ensure a dignified life for those who by legal mandate must attend the needs. The right to food is an inherent right for every person, and is covered by many laws in the world, and our legal system is not the exception because it has given priority to the right to food, especially the most vulnerable Such as children and adolescents and the protection that this group of people deserve from their parents and the state itself. Our Magna Carta is clear and specific when establishing that the upbringing of children and responsibility is only of the parents being a mandatory duty that they have to comply, otherwise the law will enforce this by enforcing the rights of the child or adolescent………..